Models with higher weak-isospin Higgs multiplets - Cheng-Wei Chiang; Kei Yagyu (Physics Letters B, 2018)
In order for scale factors κV(V=W,Z) of the 125-GeV Higgs boson couplings to have the possibilities of being greater than unity and κW≠κZ while keeping the electroweak ρ parameter unity at tree level, the Higgs sector must be extended with at least two exotic SU(2)L multiplets in addition to the doublet Higgs field in the Standard Model. By the requirements of perturbative unitarity, no Landau pole in gauge couplings, and no accidental global U(1) symmetry, we exhaust all the possible combinations of two exotic Higgs fields and derive general formulas for κV. We find that the current central values κW=1.12 and κZ=0.99 reported by CMS can be accommodated in the model with a complex and a real Higgs triplets as the simplest example.